Iron Pill-Induced Gastritis in the Paediatric Population - Daniel Ching; Cathy Mews; Charles Crompton; Madhur Ravikumar; Disna Abeysuriya (Case Reports in Pediatrics)
Iron is the most common trace mineral in the body. The effects of iatrogenic iron pill-induced gastritis (IPIG) at therapeutic levels are underreported and underappreciated in the paediatric population. Herein, we report a case of an 11-year-old boy presenting with increasing epigastric pain and refusing oral intake secondary to iron pill tablets. We report only the second confirmed case of a paediatric patient with IPIG in the peer-reviewed literature.